2001
DOI: 10.1002/mop.10081
|View full text |Cite
|
Sign up to set email alerts
|

Systematic design of resonant microstrip sensors with sensitive coating

Abstract: A parameter study of multilayered sensor structures is presented. These consist of planar microwa¨e resonators coated with a thin, sensiti¨e membrane. The influence of the¨arious layers on the sensor characteristics is studied, and design rules are formulated. Two sensors with a moisture-sensiti¨e coating are realized. The experimental results confirm the simulation. ᮊ ABSTRACT:The contribution to the induced current in a wire inside a conducting box due to field penetration through a narrow slot in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Another possible reason of discrepancy is due to the difference between, the dielectric data acquired from literature for simulation and actual dielectric values obtained from experiment. Also, it is reported that the higher humidity level in surrounding can affect the amount of resonance shift .…”
Section: Resultsmentioning
confidence: 99%
“…Another possible reason of discrepancy is due to the difference between, the dielectric data acquired from literature for simulation and actual dielectric values obtained from experiment. Also, it is reported that the higher humidity level in surrounding can affect the amount of resonance shift .…”
Section: Resultsmentioning
confidence: 99%
“…Originally, they were used as a measurement tool for the characterization of the transmission properties of microstrip lines (Troughton 1969). Previously, they have been widely used as external probes for dielectric material properties (Bernard and Gautray 1991), moisture sensors (Abegaonkar et al 1999, Pawlak et al 2002 and active or passive filter elements in microwave systems (Lu and Ferendeci 1996). At THz frequencies, however, they have not been applied as sensor elements so far.…”
Section: Introductionmentioning
confidence: 99%